Capacity management and routing policies for voice over IP traffic. - Mishra, P.P.
This article addresses the problem of designing capacity management and routing mechanisms to support telephony over an IP network. For this service, we propose two distinct architectural models. The first relies on enhancements to the basic IP infrastructure to support integrated service transport and QoS routing. The second assumes that the IP network can support an overlay virtual private network with dedicated capacity for the VoIP service, thereby allowing standard capacity management and routing mechanisms from circuit-switched networks to be reused. We evaluate the performance of these two architectural models and their-associated policies via simulations using configuration and usage data derived from operational networks
Keywords: IP infrastructure enhancement; QoS routing; VoIP service; Architectural models; Capacity management; Circuit-switched networks; Configuration data; Integrated service transport; Operational networks; Overlay virtual private network; Packet-switched network infrastructure; Performance; Routing policies; Simulations; Telephony over IP network; Usage data; Voice over IP traffic